PENGARUH PEMBELAJARAN QUANTUM DALAM PEMBELAJARAN IPA TERHADAP MOTIVASI BELAJAR DAN PENGUASAAN KONSEP SISWA KELAS IV SDN 3 PANCOR - Deni Siregar (Universitas Hamzanwadi, 2010)
This study aims to determine the effect of Quantum learning on learning motivation and mastery of science concepts of fourth grade students. This study was an experimental research conducted at SDN 3 Pancor, involving 60 students. The control group was 30 students of IV B class, the experimental group was 30 students of IVC class. The class were determined using random sampling technique. Quantum Learning is the independent variable, learning motivation and mastery of science concepts are as the dependent variables. The data were collected using questionnaire and mastery of science concepts test. The data were analyzed using Manova with the assistance of SPSS 16.0 for Windows. The result of the analyses shows that: (1) there is a significant difference in learning motivation between students learning using quantum learning and those using conventional learning (F = 26.47, p 0.05), (2) there are significant differences between the science concept mastery between students learning using quantum learning and those using conventional learning (F = 26.36, p 0.05), (3) there are significant differences in learning motivation and mastery of science concepts between students learning using quantum learning and those using conventional learning (F = 26.14, p 0,05). Quantum learning can be said to affect student motivation and the mastery of science concepts. Keywords: Quantum Learning, learning motivation, and mastery of science concepts